The Impact of the Entrepreneurial Education Ecosystem, Self-Efficacy, and Outcome Expectations on Entrepreneurial Career Interest Among Students - Amalika Akmala; Khasan Setiaji (Universitas Negeri Semarang, 2026)
Entrepreneurial career intention among university students in developing economies remains relatively low, while prior research has predominantly emphasized individual determinants and insufficiently integrated the comprehensive role of the entrepreneurship education ecosystem. This study aims to examine the effect of the entrepreneurship education ecosystem on students’ entrepreneurial career intention through the mediating roles of self-efficacy and outcome expectations. A quantitative survey design was employed involving 314 undergraduate students from the Faculty of Economics and Business, Universitas Negeri Semarang, selected using proportional random sampling. Data were analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings reveal that the entrepreneurship education ecosystem has a positive effect on both self-efficacy and outcome expectations. Furthermore, self-efficacy and outcome expectations significantly and positively influence entrepreneurial career intention. The entrepreneurship education ecosystem also demonstrates an indirect effect on entrepreneurial career intention through these two mediating variables. This study highlights the critical role of strengthening the entrepreneurship education ecosystem as a mechanism for shaping students’ confidence and perceived benefits, thereby fostering stronger entrepreneurial career orientation.